Artificial intelligence in pharmacy education: innovations and future directions / Mathumalar Loganathan - Loganathan, Mathumalar (Faculty of Pharmacy, 2025)
Artificial Intelligence (AI) is profoundly transforming pharmacy education, presenting numerous opportunities and complex challenges for pharmacy institutions worldwide. In countries like Switzerland, innovative approaches and the integration of AI in pharmacy education are reshaping the educational landscape, particularly in digital health, AI-driven pharmaceutical research, and robotics in pharmacy practice. Moreover, Switzerland is home to major pharmaceutical companies such as Novartis, Roche, and Lonza, which are heavily investing in AI for drug development and patient care. These companies collaborate with Swiss universities to integrate research and AI-based learning tools into pharmacy education. This strong academic-industry partnership positions Switzerland as a key player in AI-driven pharmacy innovation.